2017
DOI: 10.1002/aic.15975
|View full text |Cite
|
Sign up to set email alerts
|

Surface layer modification of AEMs by infiltration and photo‐cross‐linking to induce monovalent selectivity

Abstract: Surface modification of anion exchange membranes (AEMs) by attaching a negatively charged layer is the main method for preparing monovalent anion selective membranes. However, tremendous increase of membrane resistance and poor long‐term stability of the modified membranes face great challenges. In this work, a photosensitive molecule (4,4‐diazostilbene‐2,2‐disulfonic acid disodium salt [DAS]) was infiltrated into the membrane surface and immobilized in the structure by cross‐linking under UV irradiation. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 37 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…To overcome these challenges, other techniques, such as covalent immobilization of poly(ethyleneimine) (PEI) onto the surface of AEM [55], infiltration and cross-linking [57], and photoinduced covalent immobilization [58], were tested to form a stable linkage between the membrane and the modified layer. Covalent immobilization of PEI on AEM and partly quaternized poly(phenylene oxide) achieved excellent monovalent selectivity of (P Cl − SO 2− 4 = 4.…”
Section: Mg 2+mentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome these challenges, other techniques, such as covalent immobilization of poly(ethyleneimine) (PEI) onto the surface of AEM [55], infiltration and cross-linking [57], and photoinduced covalent immobilization [58], were tested to form a stable linkage between the membrane and the modified layer. Covalent immobilization of PEI on AEM and partly quaternized poly(phenylene oxide) achieved excellent monovalent selectivity of (P Cl − SO 2− 4 = 4.…”
Section: Mg 2+mentioning
confidence: 99%
“…During continuous cycling for 70 h in the ED process, the concentration of the sulphate ion was higher than the chloride ion, showing excellent monovalent ions selectivity and stability of the modified membrane. Very recently, Liu et al modified AEM with 4,4-diazostilbene-2,2-disulfonic acid disodium salt [DAS] via infiltration and then covalent cross-linking using UV radiation [57]. As shown in Figure 8, the modified membrane had a negative charge toward the surface of the AEM, exhibiting the highest permselectivity of 11.21 compared with the commercial monovalent selective membrane (Selemion ASV) [49,63] and other reported modified AEMs (see Table 2) [48,49,55,58,59].…”
Section: Mg 2+mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to support the positive effects of modifying AEMs through the two methods above-mentioned, Figure 7 shows the Fourier-transform infrared spectroscopy (FTIR) spectra and the atomic force microscope (AFM) images of a commercial AEM (JMA-II-07), which was modified by infiltration (immersion), using 4,4-diazostilbene-2,2-disulfonic acid disodium salt (DAS) as the modifying agent, and UV-cross linking [70]. The FTIR revealed that both the infiltrated (uncross-linked D-5), and UV-crosslinked (D-5) membranes exhibited sulfonate absorption bands at 1200, 1130 and 1030 cm −1 .…”
mentioning
confidence: 99%
“…Membranes 2020, 10, x FOR PEER REVIEW 15 of 22 infiltration (immersion), using 4,4-diazostilbene-2,2-disulfonic acid disodium salt (DAS) as the modifying agent, and UV-cross linking [70]. The FTIR revealed that both the infiltrated (uncrosslinked D-5), and UV-crosslinked (D-5) membranes exhibited sulfonate absorption bands at 1200, 1130 and 1030 cm −1 .…”
mentioning
confidence: 99%